Synthesis of deuterium-labeled atorvastatin and its metabolites for use as internal standards in a LC/MS/MS method developed for quantitation of the drug and its metabolites in human serum - Chen, Bang-Chi; Sundeen, Joseph E.; Guo, Peng; Bednarz, Mark S.; Hangeland, Jon J.; Ahmed, Syed Z.; Jemal, Mohammed (Journal of labelled compounds & radiopharmaceuticals, 2000)
D5‐labeled isotopomers of atorvastatin, atorvastatin lactone and its hydroxy metabolites were synthesized as internal standards for use in a LC/MS/MS method developed for the simultaneous quantitative determination of atorvastatin and its hydroxy metabolites in human serum. d5‐Atorvastatin and d5‐atorvastatin lactone were prepared from d5‐aniline whereas their corresponding hydroxy metabolites were synthesized using d5‐benzaldehyde. Copyright © 2000 John Wiley & Sons, Ltd.